DEVELOPMENT OF WEBSITE-BASED E-MODULE LEARNING MEDIA TO IMPROVE STUDENTS SCIENCE LITERACY ON EXCRETORY SYSTEM MATERIAL - Destyara, Vina; Rubini, Bibin; Awaludin, M. Taufik (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2025)
The current level of science literacy of students still tends to be low, this happens because of the limited learning media used in the learning process. The existence of learning media can be used as a tool in stimulating students thoughts, attention and abilities. This study aims to develop learning media in the form of website-based e-module that are feasible, effective and practical in improving students science literacy in excretory system material. The method used in this research is Research and Development (RD) with the ADDIE development model. This research was conducted at Taruna Terpadu High School and aimed at class XI MIPA with a total of 25 students and involved 2 biology teachers. The research design was in the form of one group pretest-posttest or using one class as an experimental class. Before being tested, the e-module was validated by media experts and material experts. The results of the assessment by media experts obtained a percentage of 100% with very feasible criteria, while the material experts obtained a percentage of 93% and 92.5% with very feasible criteria. Testing the effectiveness of e-module from the results of the N-gain calculation obtained a value of 0.73 with high criteria. After being tested, practicality testing was carried out through students and teacher response questionnaires. The teacher response questionnaire obtained a percentage of 99.5% with very practical criteria. While the students response questionnaire obtained a percentage of 90% with very practical criteria. The existence of interactive web-based e-module can increase students motivation and learning independence and increase understanding of science concepts by reading, understanding and analyzing science information critically. Based on the results of the study, it can be concluded that the website-based e-module developed is feasible, effective and practical in improving students science literacy on excretory system material.